A zero-cost attention-based approach to promote cleaner streets: A Signal Detection Theory approach in Parisian streets. - Rita Abdel Sater; Mathilde Mus; Valentin Wyart; Coralie Chevallier (PLoS ONE, 2023)
In an effort to inform interventions targeting littering behaviour, we estimate how much a change in trash-bag colour increases trash can visibility in Paris. To that end, we applied standard Signal Detection techniques to test how much changing trash-bag colour affects subjects' trash can detection rates. In three pre-registered studies, we found that changing trash bag colour from grey to either red, green or blue considerably increases the perception of bins in British (tourist) and Parisian (resident) samples. We found that changing the bag colour from grey to blue increased visibility the most.